Governance and Management Performance of Football Clubs in SFA Southwest Aceh, Indonesia - Husaini; Musran; Boihaqi, Boihaqi; Aldiansyah Akbar; Fajar Maulana (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives: This study aimed to examine the management implementation of the SFA Southwest Aceh football club and assess the extent to which club activities align with formal duties and functions, particularly regarding organizational structure, long-term program planning, and sustainability efforts. Methods: A qualitative descriptive approach was employed. Purposive sampling was used to recruit key informants from the club’s core management and athlete representation, including the chairman, coach, secretary, treasurer, and athletes (n = 4 primary informants from the core management). Data were collected through observation, documentation review, and semi-structured interviews. The data were analyzed through thematic descriptive analysis to identify patterns in administrative, financial, and training management, as well as challenges related to organizational structure and long-term strategy. Results: The findings indicate that SFA Southwest Aceh has implemented key management functions in administration, finance, and training. Administrative routines and financial reporting were functioning, and the training process was organized through systematic planning supported by efficient internal communication. However, the club’s organizational structure was not yet ideal, and long-term program planning remained limited. The club’s operational sustainability was strongly influenced by sponsorship availability and resource dependency, highlighting constraints in stable funding and strategic partnerships. Conclusion: Overall, SFA Southwest Aceh demonstrates generally good club management, particularly in administrative, financial, and training domains, despite shortcomings in organizational structure and long-term strategic planning. Strengthening governance structure, developing a clear long-term development roadmap, and establishing sustainable collaborations are essential to overcome operational barriers and support the club’s transition toward more professional and sustainable management